Recent research advances and ethno-botanical history of miang, a traditional fermented tea (Camellia sinensis var. assamica) of northern Thailand - Chartchai Khanongnuch (2018)
© 2017 Korea Food Research Institute Miang is an ethnic fermented tea leaf (Camellia sinensis var. assamica) from northern Thailand. It has a long history of sociocultural relationship with northern Thai people. Unlike other type s of tea, miang is a unique product that is known as chewing tea or eating tea. In addition, it is also a specific food for traditional religious ceremonies and funerals. Although chewing of miang has become less popular among younger generations, there remains a demand for miang in specific areas of northern Thailand. The traditional fermentation mechanism for miang has not been well documented and the information is now being developed. Current studies indicated that the astringent miang possessed higher phenolic metabolites especially epigallocatechin gallate than the sour miang and fresh tea leaf used for making miang in general. The chemical constituents in miang are of interest and the scientific advances to understand and develop this ethnic tea product are rapidly emerging. Miang has many potential benefits and is proposed to be used for many applications such as foods, pharmaceuticals, and nutraceuticals. Other valuable chemical constituents have not yet been widely reported and require further research. The current understanding of miang has been developed from literature on historic and sociocultural relationships of miang, current evidence scientific evidence, and personal interviews with local miang producers. From the plantation areas close to miang production, physiological, chemical, and microbiological analysis of miang were undertaken and integrated with current scientific literature and community surveys to build an evolving body of new knowledge. This paper provides important historic background of miang and its ethno-botanical relationship with northern Thai people. Traditional production of miang and its chemical and physical properties make miang different from other fermented tea leaves. Therefore, this unique miang with ethnic roots in northern Thailand is a potential source of health relevant bioactive compounds that is rapidly gaining research interest and can be advanced for many beneficial food and health applications.